Temporal and spatial distribution of the alpine meadow carbon budget in Gannan, China from 1969 to 2018 - Wang, Xingyu; Zhang, Meiling; Nazieh, Stephen; Nkrumah, Teddy (Frontiers in Environmental Science, 2023)
Human activities such as the burning of fossil fuels and the overuse of land have increased the concentration of greenhouse gases in the air, further exacerbating climate change, which has become a problem that humans have to face and solve. The alpine meadows in southern Gansu, China are very sensitive to climate change and play an important role in the terrestrial ecosystem. The CENTURY model was used to study the spatial distribution and changes of carbon budget in Gannan alpine meadow in Gansu in the past 50 years, which is of great significance for coping with climate change. The results show that: (1) the carbon budget in different regions presents different distribution characteristics. (2) the spatial distribution of the carbon budget changes with time, which is manifested in the different spatial distribution of the carbon budget in each study stage and in each quarter. The spatial distribution is also different. In spring, some areas in the northern part of southern Gansu are carbon sources, and in summer, autumn and winter, they are carbon sinks. The spatial distribution of the carbon budget changes with time, and it is different in each stage, but it is a carbon sink as a whole. (3) From 1969 to 2018, the Gannan alpine meadow as a whole shows a carbon sink phenomenon, and the carbon budget is a carbon sink. (4) In every year, the carbon sink shows a trend of increasing firstly and then decreasing, and the carbon sink is the largest in August. (5) Temperature and precipitation are positively correlated with NEP. (6) The total carbon sequestered in the Gannan Alpine Meadow in the past 50 years is 43580.9 gC. The annual and monthly average NEP values are about 871.62 gC/m2/yr, and 72.635 gC/m2/month, respectively.